Development of Criminal Law on Corruption in Indonesia: Historical and Legal Review - aisyah sabrina; Muhammad Ramadhan (AT-TAFAHUM: Journal of Law, 2024)
Corruption has long been recognized as an extraordinary crime in Indonesia due to its systemic nature and its detrimental impact on economic development, public welfare, and public trust in government institutions. The evolution of anti-corruption law in Indonesia reflects the state's continuous efforts to strengthen legal mechanisms for combating corruption in response to changing political and social conditions. This study aims to examine the historical development of criminal law on corruption in Indonesia and to analyze the effectiveness of anti-corruption regulations across different political periods. The research employs a normative legal method using historical, statutory, and conceptual approaches. Data were collected through library research involving primary, secondary, and tertiary legal materials, including legislation, legal literature, and scholarly publications, which were analyzed qualitatively. The findings indicate that the development of Indonesia's anti-corruption legal framework has progressed through four major phases: the colonial period, the Old Order, the New Order, and the Reform Era. Each phase reflects distinct legal and political characteristics that influenced the formulation and enforcement of anti-corruption policies. Significant legal reforms during the Reform Era, including the enactment of Law No. 31 of 1999 as amended by Law No. 20 of 2001 and the establishment of the Corruption Eradication Commission (KPK), have strengthened Indonesia's institutional capacity to combat corruption. Nevertheless, persistent challenges remain, including weak law enforcement, political intervention, institutional resistance, and attempts to weaken anti-corruption agencies. Therefore, strengthening institutional independence, improving legal certainty, and enhancing public accountability remain essential for ensuring the effectiveness of corruption eradication efforts in Indonesia.